The responsibility of public agencies in cases of accidents of workers of outsourcing companies - Morales Rivadeneyra, Bruno Jairo (2022)
The problem circumscribed in public agencies reveals a lack of regulation for those cases of accidents at outsourcing companies. Both the regulations on the matter, Act No. 27626, and its regulation, enacted by Supreme Executive Order No. 003-2002-TR, show a great difference, and that is that in one of the two regulations nothing is mentioned about public agencies, which gives open letter to interpretations on the matter and resulting in the vulnerability of workers who suffer accidents at work. Faced with this situation we ask ourselves: what causes this problem? since its impact is important because if it is solved, it could determine joint and several liability by not fulfilling the minimum obligations to provide control, safety and health to the worker, who is a fundamental part of any company or institution, since the value and human character are protected under our Magna Carta, which mentions that work is a fundamental right.